A translational neuroscience perspective on loneliness: narrative review focusing on social interaction, illness and oxytocin - Barton, Simon; Zovko, Ana; Müller, Christina; Krabichler, Quirin; Schulze, Janna; Wagner, Shlomo; Grinevich, Valéry; Shamay-Tsoory, Simone; Hurlemann, René (Neuroscience & biobehavioral reviews, 2024)
This review addresses key findings on loneliness from the social, neurobiological and clinical fields. From a translational perspective, results from studies in humans and animals are included, with a focus on social interaction, mental and physical illness and the role of oxytocin in loneliness. In terms of social interactions, lonely individuals tend to exhibit a range of abnormal behaviors based on dysfunctional social cognitions that make it difficult for them to form meaningful relationships. Neurobiologically, a link has been established between loneliness and the hypothalamic peptide hormone oxytocin. Since social interactions and especially social touch regulate oxytocin signaling, lonely individuals may have an oxytocin imbalance, which in turn affects their health and well-being. Clinically, loneliness is a predictor of physical and mental illness and leads to increased morbidity and mortality. There is evidence that psychopathology is both a cause and a consequence of loneliness. The final section of this review summarizes the findings from social, neurobiological and clinical perspectives to present a new model of the complex construct of loneliness.
Online verfügbar: 23. Mai 2024, Artikelversion: 19. Juni 2024
Gesehen am 04.02.2025